(untitled) (Scientia Agropecuaria, 2025)
During corn storage, significant losses occur due to pest attacks, especially the weevil, Sitophilus zeamais Motschulsky. This study aimed to evaluate the feeding preference of Sitophilus zeamais on seeds of stored corn genotypes. The tests were carried out in the laboratory of the Center for Scientific and Technological Development in Pest and Disease Management (NUDEMAFI) at the Center for Agricultural Sciences and Engineering of the Federal University of Espírito Santo (UFES) in Alegre, in an air-conditioned room with a maximum temperature of 26.4 and a minimum of 26.2 ºC (± 2 ºC) and humidity between 70% and 75%. A host preference test with free choice was performed on insects from Nudemafi breeding, aged 5 to 10 days, in six (6) arenas with six (6) replicates using a completely randomized design (CRD). After 96 hours, the following were evaluated for each genotype: number of insects attracted, insect weight, number of infested seeds, percentage of seed loss, and 60 days after infestation, the percentage of emerged insects, physical and bromatological composition were determined. The results showed significant differences in the preference of Sitophilus zeamais adults in relation to the maize genotypes analyzed; the lowest food preference was observed in the Purple genotype (4.1%), followed by AG1051, which obtained 8.3% respectively. The genotypes presented antixenosis due to the effect of the nutritional properties and physical hardness of the seed.